2021
DOI: 10.9734/ajee/2021/v14i430211
|View full text |Cite
|
Sign up to set email alerts
|

The Indian Antelope Nilgai (Boselaphus tragocamelus) Appropriate Contender for Domestication could add in Human Society

Abstract: The domestication of animals was part of a major transformation in the way of life of an increasing number of human societies with deep social and spiritual changes. In the present study, we report about utility of Nilgai and the values of its products and how it can add variety in our diet. Domestication of Nilgai may prove as an outstanding diet (veal and juveniles) for human and domesticated carnivores it may be the most important achievements that man-made in his cultural history. It is very useful and has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As per record total 3,228 numbers of Nilgais were killed by a professional shooters during 2017-2019 in different districts of Bihar. Some Farmers in Haryana and Bihar state also have taken to electrocuting nilgai but by and large the carcass is buried and not consumed [3,4,7].…”
Section: Availability and Impactmentioning
confidence: 99%
See 4 more Smart Citations
“…As per record total 3,228 numbers of Nilgais were killed by a professional shooters during 2017-2019 in different districts of Bihar. Some Farmers in Haryana and Bihar state also have taken to electrocuting nilgai but by and large the carcass is buried and not consumed [3,4,7].…”
Section: Availability and Impactmentioning
confidence: 99%
“…Many research workers reported and expected the suitability of the habitat for undomesticated mammals to depend on the habitat type [26,13]. We expected the home-grown population to use uninhabited / taming Nilgai as a derivation of meat, milk and other by-products for private consumption and a source of income [7,27]. They depend on the demand of the local population as well as export to other countries and the access to the market to earn money.…”
Section: Pedigree Of Food and Medicinementioning
confidence: 99%
See 3 more Smart Citations